Co-designing implementation strategies to promote remote physical activity programs in frail older community-dwellers - Villa-García, Lorena; Davey, Vanessa; Peréz, Laura M.; Soto-Bagaria, Luis; Risco, Ester; Díaz, Pako; Kuluski, Kerry; Giné-Garriga, Maria; Castellano-Tejedor, Carmina; Inzitari, Marco (Frontiers in Public Health, 2023)
Background The “AGIL Barcelona (AGILBcn)” community-based integrated care program is a multicomponent healthy aging intervention for frail older adults. In this context, the present study aimed to identify implementation strategies to optimize the accessibility, acceptability, and adaptability of mobile health (mhealth) interventions to enhance physical activity in frail older adults, and to prioritize action points according to their importance and feasibility, through a co-design process. Material and methods A mixed methods approach was used. In the qualitative phase, a method adapted from the World Café was applied in 6 virtual groups to identify strategies to facilitate the virtual physical activity program. In the quantitative phase, prioritization and feasibility of the strategies was analyzed through surveys. Strategies were ranked based on priority vs. feasibility, revealing if strategies should either be: implemented first; if possible; taken into account for future consideration; or directly disregarded. The convenience sample included older adults (n = 7), community professionals (n = 9) and health professionals (n = 13). Qualitative data were analyzed by summative content analysis and quantitative data by nonparametric descriptive analyses. Results A total of 27 strategies were identified and grouped into four categories: general strategies for reducing barriers; specific strategies for facilitating the use of a digital application; specific strategies for facilitating participation in virtual exercise groups; and specific strategies for facilitating external support. According to the ranking of strategies, the first ones to be implemented included: digital literacy, digital capability assessment, family technology support, weekly telephone follow-up by professionals, personalizing exercises, and virtual exercises in small groups. Conclusion The active participation of all stakeholders enabled us to identify potential strategies for implementing person-oriented technology in physical activity programs and for engaging older adults.